A political economy of human rights: Oil, natural gas, and state incentives to repress1. (April 2013) - DeMeritt, Jacqueline H.R.; Young, Joseph K
Oil and other natural resources are linked to many undesirable outcomes, such as civil war, autocracy and lack of economic development. Using a state-centered framework for revenue extraction, we identify why oil should also be linked to another undesirable effect: repression. We argue that repression is less costly where states do not rely on their citizenry for generating revenue, so that these states are more likely than others to use indiscriminate violations of personal integrity rights as a policy tool. We test this argument using a cross-national database with a variety of indicators of oil and fuel rents and personal integrity violations. Across all specifications and different indicators, we find a substantive and significant relationship between a state relying on oil and the violation of personal integrity rights.